Distribution of Chromophytic Phytoplankton in the Eddy-Induced Upwelling Region of the West Pacific Ocean Revealed Using rbcL Genes - Pujari, Laxman; Narale, Dhiraj; Kan, Jinjun; Wu, Chao; Zhang, Guicheng; Ding, Changling; Li, Liuyang; Sun, Jun (Frontiers in Microbiology, 2021)
Marine chromophytic phytoplankton are a diverse group of algae and contribute significantly to the total oceanic primary production. However, the spatial distribution of chromophytic phytoplankton are understudied in the West Pacific Ocean (WPO). In this study, we have investigated community structure and spatial distribution of chromophytic phytoplankton using RuBisCO genes (Form ID rbcL). Our results showed that Haptophyceae, Pelagophyceae, Cyanophyceae, Xanthophyceae and Bacillariophyceae were the dominant groups. Further, chromophytic phytoplankton were distinguished between upwelling and non-upwelling zones of the WPO. Surface and 75m depths of non-upwelling area were dominated by Prochlorococcus strains, whereas chromophytic phytoplankton were homogenously distributed at surface layer in upwelling zone. Meanwhile, Pelagomonas-like sequences were dominant at DCM (75m) and 150m depths of upwelling zone. Non-metric multidimensional scaling (NMDS) analysis did not differentiate chromophytic phytoplankton between upwelling and non-upwelling areas, however, it showed the clear trends of them at different depths. Further, redundancy analysis (RDA) showed influence of physicochemical parameters on the distribution of chromophytic phytoplankton. Along with phosphate (p < 0.01), temperature and other dissolved nutrients were important in driving community structure. Upwelling zone were impacted by a decrease in temperature, salinity, and re-supplement of nutrients, where Pelagomonas-like sequences outnumbered other chromophytic groups present.